Effects of age simulation suits on psychological and physical outcomes: a systematic review - Gerhardy, Thomas; Schlomann, Anna; Wahl, Hans-Werner; Schmidt, Laura (European journal of ageing, 2022)
Age simulation suits (ASS) are widely used to simulate sensory and physical restrictions that typically occur as people age. This review has two objectives: first, we synthesize the current research on ASS in terms of the observed psychological and physical effects associated with ASS. Second, we analyze indicators able to estimate the validity of ASS in simulating "true" ageing processes. Following the PRISMA guidelines, eight electronic databases were searched (BASE, Cinhal, Cochrane, Google Scholar, ProQuest, PsychINFO, Pubmed, and Web of Science). Qualitative and quantitative studies addressing effects of ASS interventions regarding psychological outcomes (i.e., empathy, attitudes) or physical parameters (i.e., gait, balance) were included. The Mixed Methods Appraisal Tool was applied for quality assessment. Of 1890 identified citations, we included 94 for full-text screening and finally 26 studies were examined. Publication years ranged from 2001 to 2021. Study populations were predominantly based on students in health-related disciplines. Results suggest that ASS can initiate positive effects on attitudes toward (d(weighted) = 0.33) and empathy for older adults (d(weighted) = 0.54). Physical performance was significantly reduced; however, there is only little evidence of a realistic simulation of typical ageing processes. Although positive effects of ASS are supported to some extent, more diverse study populations and high-quality controlled designs are needed. Further, validation studies examining whether the simulation indeed reflects "real" ageing are needed and should build on reference data generated by standardized geriatric assessments or adequate comparison groups of older adults. Prospero registration: 232686.
Gesehen am 25.01.2023